Senior's Social Economy - Opie, Redvers; Senior, N. W. (Quarterly Journal of Economics, 1929)
Journal Article Senior's Social Economy Get access Redvers Opie Redvers Opie Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 43, Issue 2, February 1929, Pages 363–375, https://doi.org/10.2307/1882479 Published: 01 February 1929